Risk Identification, Assessment and Management in The Greek Public Hospitals: The Contribution of The Board of Directors and Internal Audit - Andreas G. Koutoupis; Paraskevi N. Koufopoulou; Dimitrios I. Antonoglou; Athanasios P. Vozikis (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - Our study examines the development of a reliable internal audit plan in the Greek public hospitals, focusing on how to identify, assess and evaluate the relevant risks by the Boards of Directors. Data - We use an exceptional database drawing information from a large sample of Greek hospitals based on a structured questionnaire for the period from September 1, 2015 to March 31, 2017. Tools - As our primary source of data we conduct interviews with CAEs of Greek hospitals', while secondary data sources come from corporate governance codes, COSO framework for ERM, Greek corporate governance laws, regulations, best practices and published articles. Findings - Taking into account the financial crisis of the last ten years in Greece as well as the pathogenesis of the healthcare system, we note the poorly organized risk management in Greek hospitals. The results show that the financial crisis had a direct impact on the way risk management of public hospitals operates. Furthermore, we observe denial of the application and implementation in the form of formal guidelines to the members of the hospitals' Board of Directors. Contribution - Research findings can have a catalytic effect on hospital management and those who implement public policies.
Keywords: A34; B12; B13; B62; 650; Enterprise Risk Management; Internal Audit; Hospitals